Trigger of Bronchial Hyperresponsiveness Development may not always need Eosinophilic Airway Inflammation in Very Early Stage of Asthma. Issue 1 (March 2016) - Obase, Yasushi; Shimoda, Terufumi; Kishikawa, Reiko; Kohno, Shigeru; Iwanaga, Tomoaki
Background: Cough variant asthma (CVA), a suggested precursor of standard bronchial asthma (SBA), is characterized by positive bronchial hyperresponsiveness (BHR) and a chronic cough response to bronchodilator that persists for >8 weeks. Objective: Airway inflammation, BHR, and airway obstructive damage were analyzed to assess whether CVA represents early or mild-stage SBA. Methods: Patients with newly diagnosed CVA (n = 72) and SBA (n = 84) naive to oral or inhaled corticosteroids and without exacerbated asthma were subjected to spirometry, impulse oscillometry, BHR tests, sputum induction, and fractional exhaled nitric oxide measurements. Results: In the patients with CVA, spirometry demonstrated higher forced expiratory volume in 1 second (FEV1 ) to forced vital capacity ratio, FEV1 percent predicted, flow volume at 50% of vital capacity % predicted, and flow volume at 25% of vital capacity % predicted values, and impulse oscillometry demonstrated lower R5 –Z20, AX, and Fres, and higher X5 values. In addition, the fractional exhaled nitric oxide and sputum eosinophil numbers were lower and the PC20 was higher than in patients with moderate SBA. However, these factors were similar in the patients with CVA and in the patients with intermittent mild SBA. A significantly smaller proportion of the patients with CVA had increased sputum eosinophils than the patients with intermittent mild SBA (p < 0.0001). However, interestingly, among the patients with CVA, no significant differences in the PC20 values were found between the patients with and those without increased sputum eosinophils. Conclusions: All measures of central and peripheral airway obstruction, eosinophilic inflammation, and airway hyperresponsiveness in patients with CVA were milder than in patients with moderate SBA but were similar to those of patients with intermittent mild SBA. In CVA, the BHR was not affected by airway eosinophilic inflammation, which indicated that the very early development of BHR may not always need airway eosinophilic inflammation.